A concept to assess the costs and benefits of renewable energy use and distributional effects among actors: The example of Germany. Issue 1 (February 2016) - Breitschopf, Barbara; Held, Anne; Resch, Gustav
This paper describes a concept for the detailed assessment of the costs and benefits of renewable energy technologies deployment. A first quantitative impact assessment of German renewable energy technologies use is conducted from a historical perspective based on this comprehensive method. It includes costs and benefits at three different levels – energy system, micro- and macro-economic. The findings suggest that, at the system level, the generation costs in the electricity and heat sector are partly compensated by positive effects mainly from avoided emissions due to the use of renewable energy technologies in the electricity and heat sector. On the electricity market, small power consumers bear a very large share of the policy costs, while others might even profit from renewable energy technologies use. However, a comprehensive assessment that accounts for all the different negative and positive effects in the long term, including distributional effects, is more challenging. The concept applied here allows a differentiated comparison of a wide range of effects including aggregated costs and benefits as well as how these are distributed across different economic actors.